Comparative Study on the Genetics Importance of Onion (Allium cepa) Cell Division under Salt Stress - Gontariu, Ioan; Pelinari, Paraschiva-Alexandra; Iorgu, Elena-Iulia; Hoffman, Dan (European Journal of Applied Sciences, 2025)
Genetic material is the most important component in the structure of a cell as it contains genetic information which all along the cell division must be correctly distributed and propagated in the next generations, this process being faultless. Thus, genetic material is compressed and stocked with the help of some histone and non-histone proteins, forming the chromosomes. The species of the Allium genus have got a variety of cytogenetic characteristics, genomes of different sizes, karyotypes with a different number of chromosomes and polyploidies. Within this type, there are significant genome variations due to the activity of DNA sequences which can change their place in the genome. The main factors influencing these factors are the transposable elements, these ones playing an important role in genome evolution due to the link between their high number and the chromosome size wherein they move to, with the help of which they form control and elimination mechanisms.